The successful management of a cardia hamartomatous inverted polyp via endoscopic submucosal dissection: a case report - Zhang, Xu; Pan, Hong-nian; Wang, Xiu-zhong; Li, Mei; Liu, Jie; Liu, Xiao-yan (Frontiers in Surgery, 2025)
BackgroundA gastric hamartomatous inverted polyp (GHIP) is an uncommon submucosal neoplasm that is histopathologically defined by a submucosal inverted growth of cystically dilated hyperplastic gastric glands.Case presentationA 74-year-old Chinese man presented with a submucosal tumor (SMT) in the cardia, identified through electronic gastroscopy. This report presents a case of cardia hamartomatous inverted polyp (CHIP), which represent a rare histological variant of gastric polyps that pose diagnostic challenges. The endoscopic examination revealed the presence of a submucosal tumor, and endoscopic ultrasonography indicated a heterogeneous tumor predominantly situated within the third (submucosal) layer. Immunohistochemistry outcomes indicated MUC5AC (+), MUC6 (+), Syn (+), Ki-67 (+, approximately 5%), Desmin (+), SMA (+), as well as MUC2 (−). To achieve en bloc resection for lesions >1.0 cm, endoscopic submucosal dissection (ESD) was performed. The pathological evaluation confirmed the diagnosis of CHIP. The patient was discharged without experiencing any complications.ConclusionTherefore, the ESD approach may be particularly suitable for the management of SMT-type hamartomatous inverted polyps.